The administration of justice in medieval Egypt : from the seventh to the twelfth century - Lev, Yaacov (Edinburgh University Press, 2020)
This book shows how political and administrative forces shaped the way justice was applied in medieval Egypt. It introduces the model that evolved during the 7th to the 9th centuries, which involved 4 judicial institutions: the cadi, the court of complaint, the police/shurta and the Islamized market law.
Keywords: Justice, Administration of -- Egypt -- History.; Law, Medieval.; Droit médiéval.; HISTORY -- Middle East -- Egypt.; Justice, Administration of; Law, Medieval; Egypt; Electronic books.; History